Effects of Bentonite Nanoplatelets and Low Magnetic Field Intensity on the Pore Structure of Polyacrylamide Gel - I Adeleke, Abayomi; M. Rajabali, Mustafa; R Sanders, Jonathan; E. Arce, Pedro (New Environmentally-Friendly Materials, 2025)
This study investigates the effects of low-intensity magnetic fields and nanoplatelet incorporation on the structure and transport behavior of polyacrylamide (PAAM) gel matrices. Gel nanocomposites containing environmentally benign montmorillonite (MMT) nanoplatelets were prepared under controlled magnetic field orientations during gelation and compared with pure PAAM reference gels. The resulting materials were characterized using polyacrylamide gel electrophoresis (PAGE), scanning electron microscopy (SEM), and MATLAB®-based quantitative image analysis to evaluate changes in pore morphology and connectivity. Relative to pure, non-magnetized PAAM gels, magnetically treated PAAM–MMT nanocomposites exhibited more uniform microstructures with reduced characteristic pore sizes. In comparison to nanocomposites prepared without magnetic-field exposure, magnetically treated gels displayed distinct shifts in pore size distributions and corresponding changes in protein mobility, indicating that low-intensity magnetic fields can modify gel microstructure through nanoplatelet redistribution or partial alignment. Orientation-dependent effects were observed, with magnetic fields applied perpendicular to the direction of protein migration producing more pronounced microstructural and transport changes than parallel orientations. The magnitude of these effects increased with nanoplatelet concentration, demonstrating a coupled dependence on filler loading and magnetic field orientation. Overall, the results establish a relationship between nanoplatelet concentration, magnetic field orientation, gel microstructure, and transport behavior in PAAM gels, demonstrating a materials-centric, low-field strategy for tuning polymer gel structure without chemical modification.